Potential Benefits on Impairment of Endothelial Function after a High-Fat Meal of 4 Weeks of Flavonoid Supplementation. (5th June 2011) - Barringer, T. A.; Hatcher, L.; Sasser, H. C.
Abstract : Studies with foods high in flavonoids have demonstrated improvement in endothelial function. We investigated whether 4 weeks of flavonoid supplementation would prevent an adverse impact on endothelial function of a high-fat meal. Endothelial function was measured by reactive hyperemia peripheral arterial tonometry (RH-PAT). The RH-PAT index was measured both before and 3 h after a high-fat meal, in 23 healthy volunteers. Subjects were randomized in a double-blind, cross-over design to 4 weeks of daily supplementation with OPC-3, or a matching placebo. RH-PAT index before and after the high-fat meal was measured at the beginning and end of each 4-week treatment phase. The high-fat meal caused a decline in endothelial function at baseline in the placebo (-10.71%, P = .006) and flavonoid [-9.97% ( P = .077)] groups, and there was no difference in decline between arms ( P = .906). The high-fat meal produced a decline after 4 weeks of placebo [-12.37% ( P = .005)], but no decline after 4 weeks of flavonoid supplement [-3.16% ( P = .663)], and the difference between the two responses was highly significant ( P < .0001). Within-group comparisons revealed no difference in endothelial function decline in the placebo arm between baseline and 4 weeks [-10.71% versus -12.37% ( P = .758)]. In the flavonoid supplement arm, the difference in endothelial function decline between baseline and 4 weeks was -9.97% versus -3.16%, but did not reach statistical significance ( P = .451). These results suggest that the flavonoid supplement used in this study mitigates the impairment of endothelial function caused by a high-fat meal. Whether certain subpopulations derive greater or lesser benefit remains unclear.